Convergences and Divergences of the Law of Non- Compliance of the German Civil Code with the Principles of European Law of Contracts and Other International Texts - Barcia Lehmann, Rodrigo (2018)
The aim of the proposed investigation is to revise critically the German reform of the obligations (2002), establishing its main implications and relevance within the process of unification of European Law obligations and contracts, and especially of the so-called soft law.